Play And Learn In Early Children To Improve Ability To Know Taste And Shape - Daulay, Maulida Rahmah; Khairani; Sitorus, Suriani; Luthfi, Mukhyar; Saragih, Aulia Ananda Putri Suhada; Nasution, Fauziah (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
Playing while learning is the principle of learning for early childhood through play skills making milk candy is a skill to observe in carrying out experiments and communicate it. In the learning process that is applied to children, educators can use learning methods that are set for children and children who are active in the learning process directly. Educators can apply it through the experimental method of making milk candy from simple ingredients and through playing this milk candy experiment educators can apply how to make milk candy and improve their ability to recognize the color, taste and shape of the milk candy. so that the child is able to name the various colors and flavors of the milk candy with the results of the simple experiment of experimenting with milk. This study uses literature study research from several journals and other books which provide sources of information that discuss milk candy.